Exploring Crystal Engineering for Porous Uranyl–Organic Frameworks: Insight into Hydrolysis and In Situ Reaction, Structural Variation‐Dependent Physical Properties. Issue 10 (7th July 2016) - Song, Jian; Xing, Yong‐Heng; Wang, Xiao‐Min; Gao, Xue; Wang, Zhi‐Nan; Feng, Xiao‐Dong; Bai, Feng‐Ying
Abstract: Three porous uranyl complexes {(CH3 )2 NH2 [(UO2 )(L1 )]⋅H2 O}n (1), {[(UO2 )5 ( μ 2 ‐OH)( μ 3 ‐OH)(L2 )2 (H2 O)3 ]}n (2) and {[(UO2 )4 ( μ 3 ‐OH)2 (L3 *)3 ]}n (3 ), { H3 L1 = 5‐((4‐carboxybenzyl)oxy)isophthalic acid, H4 L2 = 4, 4'‐oxydiphthalic acid, and H2 L3 = 4, 4'‐((6‐chloro‐1, 3, 5‐triazine‐2, 4‐diyl)bis(azanediyl))dibenzoic acid}, have been designed and synthesized under solvothermal and hydrothermal reaction conditions. All of these ligands are firstly used in the syntheses of uranyl hybrid materials. We investigated the main factors on the uranyl hydrolysis systematically and discussed the in situ reaction mechanism in detail. Furthermore, physical properties of these uranyl complexes are dependent on structural variations, such as unusual solvent‐impressionable five‐peak photoluminescence for2, surface photoelectric behavior as potential p ‐type semiconductors for2 and3, and the remarkable superiorities toward selective removal of dye pollutant for the anionic framework1 compared with the neutral ones2 and3 . Abstract : Three porous uranyl–organic frameworks were successfully designed and synthesized by utilizing a series of aromatic polycarboxylate ligands. We investigated the main factors on the uranyl hydrolysis systematically and discussed the in situ reaction mechanism in detail. Furthermore, physical properties of these uranyl complexes are dependent on structural variations, including photoluminescence, surface photoelectric behavior and selective removal of dye pollutant.